Venezuela - Wardrope, William (Milwaukee, WI : Gareth Stevens Pub., 2003)
An overview of Venezuela that includes information on its geography, history, government, language, culture, and current issues.
Includes bibliographical references and index.
Keywords: Venezuela -- Juvenile literature; Venezuela